Maqasid al-Shari'ah vis-a-vis town planning - Md Dali, Norimah; Abdullah, Alias; Ahmad Sarkawi, Azila (Pusat Tamhidi, Universiti Sains Islam Malaysia, 2016)
Town planning practices in Malaysia is based on the British system. Therefore concepts of liveability, sustainability, and quality of life have been customized according to Western values; least reflecting the Maqasid al-Shari’ah (Objectives of Islamic Law). While the former revolve on the economy, social, environment, physical and political considerations, the latter aspire to safeguard and protect human religion, life, intellect, progeny, and wealth. This article advocates the incorporation of these five elements into Town planning practices in Malaysia. The author coins this approach as Liveability Planning. Islamisation of the plan preparation system is deemed timely since Malaysia is a predominantly Muslim nation and its peoples have been pronouncedly more inclined towards the Islamic way of life since the early 70s. Islamic values should be incorporated into the National Physical Plan, Structure Plans, Local Plans and Special Area Plans and finally all Planning Standards should pave towards creating an Islamic Built Environment. The insights of this prowess have been supported by the finding of face-to-face interview sessions and semi-structured opinion surveys involving 25 senior professional Town Planners, both in the public as well as the private practice. The finding was the outcome of the ATLAS.ti.7 technique employed in this study. It points to the future of town planning system paving towards the inclusion of the Islamic framework of Maqasid al-shariah.